At the Boundaries of Authority and Authoritarianism in the Welfare State: News Coverage of Alt. Health Influencers During the Covid-19 Pandemic. Issue 1 (2nd January 2023) - Mortensen, Mette; Nørgaard Kristensen, Nete
Abstract : Battles over who holds authority to speak on health issues have been recurrent since the outbreak of Covid-19. This article investigates how the voices of alt. health influencers have been handled within the news-mediated public sphere during the pandemic. Alt. health influencers illustrate how new forms of authority are claimed and negotiated on social media, and how their ideas circulate quickly in the broader public discourse with potential risks to health, security, and stability. We focus on the Nordic welfare context, which is characterised by citizens putting great trust in societal institutions such as politics, healthcare, and professional news media. In the news coverage, the arguments of alt. health influencers have been consistently disputed by the experts and authorities of the welfare state, including the news media themselves. This has created a polarised debate. Alt. health influencers have criticised the news media, health authorities, big tech, etc. for having authoritarian traits. Meanwhile, they themselves have promoted authoritarian lines of thinking by contesting democratic forms of governance, professional news media, and scientific knowledge. This study ultimately shows that even in a high-trust, consensual welfare state, the boundaries between authority and authoritarianism are up for debate.